Spatiotemporal Distributions and Source Apportionment of PM2.5‐Bound Antimony in Beijing, China. Issue 16 (18th August 2022) - Yang, Chenmeng; Wu, Yunjie; Zhang, Leiming; Sun, Guangyi; Yao, Heng; Li, Zhonggen; Bi, Xiangyang; Huang, Qiang; Feng, Xinbin
Abstract: Antimony (Sb) is a toxic heavy metal, and PM2.5 ‐bound Sb (SbPM2.5 ) in the air impacts human health via inhalation pathways. In this study, we analyzed multiyear measurements of ambient SbPM2.5 in Beijing to characterize its spatiotemporal distributions, identify main sources, and predict future trends. The results show that ambient SbPM2.5 has been decreasing with fluctuations from 2005 to 2012 and decreased rapidly after 2013, which was likely a result of the government's enhanced air pollution control plan that targeted main sources of industrial Sb. Across the city, average SbPM2.5 concentrations were relatively higher at nonemission locomotive traffic sampling sites and in densely populated areas (9.45–19.45 ng/m 3 ) and lower in background areas (0.6–0.9 ng/m 3 ). Regional‐scale emissions and local human activities both affected the spatial distributions of SbPM2.5 . Notably, SbPM2.5 concentration increased by 58.3% from 2006 to 2013 in one suburban background area, indicating the changing emission distributions and intensities over the study period. A neural network model was developed and tested to predict future SbPM2.5 levels, results from which showed that with simulated massive reductions in coal supplies and a rapid boom in the waste incineration industry, SbPM2.5 concentration would vary in a smaller range (from 4.08 to 4.38 ng/m 3 ) over the next decade as compared to the observed range during 2011–2018 (19.0–5.44 ng/m 3 ). The impact of the continued expansion of the waste incineration industry on SbPM2.5 pollution needs to be considered in future emission control policies. Plain Language Summary: Long‐term exposure to antimony (Sb) and related compounds, such as through respiration of Sb containing atmospheric particles, can result in negative health impacts to human body. Knowledge of concentration levels and future trends of Sb in PM2.5 (SbPM2.5 ) especially in populated megacities is needed in assessing the potential risks of atmospheric Sb to human health. In this study, SbPM2.5 concentration data in Beijing over the past 15 years were aggregated to assess its past trends and predict its future levels. Benefited from the implementation of stringent air pollution control programs in this region, SbPM2.5 concentrations have been decreasing, but with fluctuations from 2005 to 2012, and at a faster rate after 2013. However, the decreasing trend will likely slowdown in the next decade due to the rapid development of the waste‐to‐energy conversion industry, which is an important source of atmospheric SbPM2.5 emission. Thus, future SbPM2.5 levels may still pose a threat to human health, especially to infants and children. Key Points: Characteristics of PM2.5 ‐bound antimony in Beijing have been summarized over 15 years and they predict future trends The aggressive reduction of antimony (Sb) pollution levels is mainly influenced by a comprehensive air pollution control program by the government The Sb emissions from waste incineration are likely to replace coal combustion as the primary source in PM2.5 now and in the next decade